2014
DOI: 10.1071/ch14060
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characteristics of Energetic Materials Based on 1,2-Dinitroguanidine

Abstract: A series of energetic salts based on 1,2-dinitroguanidine were successfully synthesised and fully characterised using 1H NMR, 13C NMR, and IR spectroscopy, mass spectrometry, elemental analysis, and differential scanning calorimetry. The results show that all the salts possess higher detonation properties (detonation pressures and velocities ranging from 24.8 to 30.3 GPa and 7665 to 8422 m s–1, respectively) than those of trinitrotolouene (TNT, 2,4,6-trinitromethylbenzene). The thermal stability and thermal ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the other hand, the topic of 1,2-dinitroguanidine salts was also explored in Ref. [71]. The authors presented the synthesis of six new compounds with mono-, di-and triaminoguanidine cations and three high-nitrogen heterocyclic cations.…”
Section: Further Nitration Of Nitroguanidinementioning
confidence: 99%
“…On the other hand, the topic of 1,2-dinitroguanidine salts was also explored in Ref. [71]. The authors presented the synthesis of six new compounds with mono-, di-and triaminoguanidine cations and three high-nitrogen heterocyclic cations.…”
Section: Further Nitration Of Nitroguanidinementioning
confidence: 99%
“…Researchers also demonstrated that the moisture stability of 1,2‐dinitroguanidine (DNG) and 1,1‐diamino‐2, 2‐dinitroethene (FOX‐7), were superior to that of 1,2‐dinitrourea (DNU) (Figure ). Then, it led to the idea of replacing the oxygen atoms from the carbonyl position by other energetic functional atoms or groups to improve the stability.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, 1,1-diaminoethene and guanidine ( Figure 2) consist of this type of structure with high nitrogen content of 48.23% and 71.14% respectively, and exist a large amount of C-N or N-N chemical bonds. To our knowledge, 1,1-diaminoethene and guanidine as energetic materials were mainly expressed in the following form: 1,1-diamino-2,2-dinitroethene, 8,9 1,2,3-triaminoguanidine, 10 1,2-dinitroguanidine, 11 energetic salts [12][13][14][15][16][17] and 1,1-diamino-2,2dinitroethene or guanidine based individual explosives ( Figure 2). 18,19 Although there are many species of 1,1-diaminoethene or guanidine based energetic materials, each has different advantages and disadvantages with respect to the stabilities and deto nation properties.…”
Section: Introductionmentioning
confidence: 99%